2004
DOI: 10.1021/bp034314c
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Structured triacylglycerols (ST) enriched in eicosapentaenoic acid (EPA) in position 2 of the triacylglycerol (TAG) backbone were synthesized by acidolysis of a commercially available EPA-rich oil (EPAX4510, 40% EPA) and caprylic acid (CA), catalyzed by the 1,3-specific immobilized lipase Lipozyme IM. The reaction was carried out in a packed bed reactor (PBR) operating in two ways: (1) by recirculating the reaction mixture from the exit of the bed to the substrate reservoir (discontinuous mode) and (2) in cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…A major benefit of many lipases is their regiospecificity to the sn-1,3 positions, where the ester group at sn -2 remains unchanged [3]. The sn-1,3 -specific lipases have been used to incorporate M fatty acids, such as caprylic (C8:0) and capric (C10:0) acids, into the TAG of several vegetable and fish oils, resulting in SL with important clinical and nutritional properties [11], [12], [13], [14], [15]. However, the industrial use of lipases has been limited by their high production costs [16], [17].…”
Section: Introductionmentioning
confidence: 99%
“…A major benefit of many lipases is their regiospecificity to the sn-1,3 positions, where the ester group at sn -2 remains unchanged [3]. The sn-1,3 -specific lipases have been used to incorporate M fatty acids, such as caprylic (C8:0) and capric (C10:0) acids, into the TAG of several vegetable and fish oils, resulting in SL with important clinical and nutritional properties [11], [12], [13], [14], [15]. However, the industrial use of lipases has been limited by their high production costs [16], [17].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Gonzáles Moreno et al . ( 108 ) reported that incorporation of caprylic acid into fish oil using PBR was higher in continuous flow than in the discontinuous flow (recycling flow). In addition, a higher EPA content was achieved in continuous flow.…”
Section: Reactor For Mlm Structured Lipid Synthesismentioning
confidence: 99%